2001
DOI: 10.1093/bja/87.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of portal triad clamping on haemodynamic conditions during laparoscopic liver resection

Abstract: To evaluate the haemodynamic effects of portal triad clamping (PTC) during laparoscopic liver resection, 10 patients without cardiac disease were studied by invasive monitoring including a pulmonary artery catheter and were compared with a control group of 10 patients undergoing liver resection by laparotomy. During laparoscopic surgery, intra-abdominal pressure was kept below 14 mm Hg and minute ventilation was adjusted to prevent hypercapnia. Measurements were made before PTC (T1), 5 min after PTC (T2) and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…Pneumoperitoneum increases mean arterial pressure and systemic vascular resistance and decreases cardiac output, modifications similar to those observed in chronic heart failure [7,28]. Similar haemodynamic alterations occur with portal clamping [18,29].…”
Section: Discussionmentioning
confidence: 55%
“…Pneumoperitoneum increases mean arterial pressure and systemic vascular resistance and decreases cardiac output, modifications similar to those observed in chronic heart failure [7,28]. Similar haemodynamic alterations occur with portal clamping [18,29].…”
Section: Discussionmentioning
confidence: 55%
“…12 A recent prospective study from our unit showed the same hemodynamic tolerance of Pringle maneuver during laparoscopy with pneumoperitoneum and laparotomy. 13 In addition, we have not observed clinically significant gas embolus in our experience with laparoscopic liver resection, despite monitoring with transesophageal echocardiography. This may be due to the high solubility of carbon dioxide.…”
Section: Commentmentioning
confidence: 59%
“…More trocars should be used to have the operating instrument always in the line of the liver transection plane. It has been shown that the clamping of the hepatic pedicle is well tolerated in hepatic resections by laparoscopy [4,6,7,20]. This was not used in our experience.…”
Section: Discussionmentioning
confidence: 90%